Estrategias inclusivas mediada por las tic para la formación de estudiantes con discapacidad visual (2022)
This research seeks to propose inclusive strategies mediated by ICT for the training of students with visual disabilities. It is based on the emerging paradigm, with a mixed approach, descriptive inductive method and non-experimental design. With an intentional population of 7 basic primary education students with visual disabilities and 5 teachers from the I.E. La Gaitana of basic primary education in Huila (Colombia), data were collected through non-participant observation, structured survey, focus group and documentary review. With instruments, strategies and resources evaluated and validated by two experts, this research makes useful strategies visible for the development of an inclusive education in students with visual disabilities. Among the main findings, it was detected that the teachers are not trained and do not have the optimal tools, and the students have a low level of disability. In conclusion, the implementation of suitable inclusive typhlotechnological strategies is necessary.